A new species of Mitius Gorochov, 1985 (Orthoptera: Gryllidae; Gryllinae) from China - Yuan, Wei; Ma, Libin; Gu, Jun-Jie (Zootaxa, 2022)
Mitius was initially described by Gorochov in 1985, using Gryllus flavipes (=Mitius flavipes) Chopard, 1928 as the type species. To date, nine species have been discovered across the world (Storozhenko, Kim & Jeon, 2015; Cigliano et al. 2021). Mitius castaneus (Chopard, 1937) and Mitius vaturu (Otte & Cowper, 2007) have truncate frons similar to Loxoblemmus Saussure, 1877, while the remaining seven species (Mitius blennus (Saussure, 1877), Mitius enatus Gorochov, 1994, Mitius eryuanensis Yuan, Xie & Liu, 2021, M. flavipes, Mitius minor (Shiraki, 1911), Mitius minutulus Yang & Yang, 1995, and Mitius splendens (Shiraki, 1930)) have a standard round frons. A new species with truncate frons that was discovered in Xizang autonomous region, China is described and illustrated in this paper.